The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1097/00007890-199807270-00002
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Ischemic Preconditioning on Liver Preservation-Reperfusion Injury in Rats

Abstract: The current results show that ischemic preconditioning protects the liver graft from subsequent long-term cold preservation-reperfusion injury in a rat liver transplantation model. The protective role of ischemic preconditioning may be mediated by the endogenous production of NO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
134
1
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(146 citation statements)
references
References 24 publications
7
134
1
4
Order By: Relevance
“…2,[30][31][32][33] We examine the available evidence and attempt to provide some potential reasons for this disparity.…”
Section: Disparity Between the Bench And Bedsidementioning
confidence: 99%
See 3 more Smart Citations
“…2,[30][31][32][33] We examine the available evidence and attempt to provide some potential reasons for this disparity.…”
Section: Disparity Between the Bench And Bedsidementioning
confidence: 99%
“…The merits of this composite endpoint were discussed in the Severity of Ischemia and RP Injury section, subsection Liver Transplantation. Remote preconditioning via limb ischemia 81,82 (1) Applicable to DCD donors; (2) Inexpensive Hypertonic saline dextran 83,84 (1) Volume enhancement, especially in donors and applicable to DCD donors; (2) Inexpensive Anesthetic preconditioning (volatile anesthetics, nitric oxide) 3,4,85 (1) May not be feasible in all donor hospitals; (2) Nitric oxide is expensive Pharmacologic preconditioning (nitrites, adenosine, interleukin-10) 2,6,7 (1) More expensive; (2) Potential side effects of agents NOTE: In contradistinction to ischemic preconditioning, all listed modalities are applicable in both liver donors and recipients. They share avoidance of direct organ ischemia and, when used in deceased donors, have the potential to benefit recipients of many organs.…”
Section: Criteria and Reporting Of Rp Injurymentioning
confidence: 99%
See 2 more Smart Citations
“…Preconditioning also appears to be a useful strategy against the deleterious effects of cold storage-reperfusion injury, since it was observed that ischemic-preconditioned grafts had reduced levels of transaminases and TNF-␣, as well as augmented bile flow and improved tissue blood flow [92][93][94]. Accordingly, in a recent publication it was observed that preconditioned rat livers were more tolerant against cold-storage-reperfusion injury, most probably due to a decreased production of O 2 Ϫ• by Kupffer cells.…”
Section: Protective Mechanisms Of Delayed Ischemic Preconditioningmentioning
confidence: 99%